WATER SUPPLY AND WASTE DISPOSAL PROBLEMS AT REMOTE AIR FORCE SITES IN ALASKA - Baumgartner, D. J. (1963)
A review of some of the water supply and waste disposal problems at remote Air Force sites is presented. Some of these problems directly affect health and well being. Others concern unaeesthetic conditions and lack of convenience, and although less critical, they still influence man's ability to function effectively in cold environments. Specific problems and their solutions are discussed and illustrated. Examples include: (1) Color removal-the color removal facility at the Middleton Island water supply and its application to the other sites; (2) Iron removal-progress in the design of a compact and simple iron removal facility for use at remote sites; (3) Disposal of waste in areas where water is not readily available-the aerobic recirculat ing waste treatment system for conservation of water and disposal of wastes; and (4) Oil car riage-sewage incineration method of waste disposal used at Pt. Barrow. Presented at the Eleventh Alaskan Science Confer ence, Alaska Div., American Association for the Advancement of Science, 30 Aug 1963, at Anchorage, Alaska.